DEVELOPING ENGLISH SUPPLEMENTARY LOCAL WISDOM-BASED LISTENING MATERIALS USING NATURAL READER 14 APPLICATION - Suryani L; Putra I N.A.; Artini L.P. (Universitas Pendidikan Ganesha, 2019)
This study aimed at a) describing the topics needed to be developed for English supplementary local wisdom-based listening materials for the eighth grade students based on Curriculum 2013 at SMP Negeri 2 Singaraja; b) describing the process of developing the English supplementary local wisdom-based listening materials for the eighth grade students at SMP Negeri 2 Singaraja; c) assessing the quality of the developed product. This study implemented Design and Development research by Richey and Klein (2007). The phases were analysis, design, development, and evaluation. The data were obtained from document study, observation sheet, interview guide, questionnaire and a scoring rubric. The data were analyzed qualitatively and quantitatively. The results of this study show that (a) the developed topics are (1) giving and responding to compliment, (2) asking and giving opinions, (3) asking and giving information about ability and willingness, (4) asking and giving information about a must, prohibition, and suggestions, (5) asking and giving instruction, invitation, and permission, (6) asking and giving information about special events or days, (7) asking and giving information about the location, things, and animals; (b) the processes of developing the materials are analyzing the English syllabus, four potencies of local wisdom of Bali, and present situation at SMPN 2 Singaraja, designing a blue print of the product, developing a blue print into a complete listening materials, and evaluating the developed materials by four expert judges; (c) the result of product evaluation done by the four expert judges shows that the developed product is categorized as excellent materials. The outcome of this study is the product which is in the form of audio recording (CD-RW) and the printed listening materials along with the answer key and listening scripts.